Point-of-care, goal-directed management of bleeding in trauma patients - Zipperle, Johannes; Schmitt, Felix; Schöchl, Herbert (Current opinion in critical care, 2023)
PURPOSE OF REVIEW: The purpose of this review is to consider the clinical value of point-of-care (POC) testing in coagulopathic trauma patients with traumatic brain injury (TBI) and trauma-induced coagulopathy (TIC). - RECENT FINDINGS: Patients suffering from severe TBI or TIC are at risk of developing pronounced haemostatic disorders. Standard coagulation tests (SCTs) are insufficient to reflect the complexity of these coagulopathies. Recent evidence has shown that viscoelastic tests (VETs) identify haemostatic disorders more rapidly and in more detail than SCTs. Moreover, VET results can guide coagulation therapy, allowing individualised treatment, which decreases transfusion requirements. However, the impact of VET on mortality remains uncertain. In contrast to VETs, the clinical impact of POC platelet function testing is still unproven. - SUMMARY: POC SCTs are not able to characterise the complexity of trauma-associated coagulopathy. VETs provide a rapid estimation of underlying haemostatic disorders, thereby providing guidance for haemostatic therapy, which impacts allogenic blood transfusion requirements. The value of POC platelet function testing to identify platelet dysfunction and guide platelet transfusion is still uncertain.
Gesehen am 10.06.2024